Pengaruh Citra Merek Dan Labelisasi Halal Terhadap Keputusan Pembelian Produk Pizza Hut Di Kota Pasuruan - Agustina, Silvia (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
Abstract : Current consumer demand for fast food (fast food) has increased. Fast food restaurants are one of the food service companies that are in demand by consumers in big cities, one of which is restaurants with foreign brands. However, this is inversely proportional to the people in Pasuruan City, where restaurants with foreign brands sometimes get a bad response,due to the emergence of public skepticism that questions the halalness of a product.This study aims to determine how the influence of brand image and halal labeling on purchasing decisions for pizza hut products in Pasuruan city. The population used by the people of Pasuruan City who have purchased pizza hut products more than once. The technique used was purposive sampling with a total of 60 respondents. Based on the results of the multiple linear regression equation, namely Y = - 0.247 + 0.734X1 + 0.289X2 , the results of this study indicate that brand image and halal labeling have a value of Fcount > F table, namely 75,457 > 3,155 and a sig. 0.000 < 0.05. The brand image variable has a tcount > ttable value, namely 11,744 > 2,002 with a sig value of 0.000 <0.05, while halal labeling has a tcount > ttable value, namely 8,867 > 2,002 with a sig. 0.000 < 0.05. Based on the results of this study it was concluded that brand image and halal labeling have a significant effect on purchasing decisions.